Penerapan Standard Costing untuk Analisis Varians Biaya Produksi pada Industri Sigaret Kretek Tangan (SKT) - Ashari, Muhammad Hasyim; Wahyudi, Ika Juliana (Magister Manajemen Universitas Wisnuwardhana, 2026)
Abstract. This study aims to analyze the variance of production costs at CV RBA. The research employed a quantitative method with a descriptive approach to evaluate the differences between standard production costs and actual production costs. The findings indicate that the direct labor cost component experienced the most significant variances, both favorable and unfavorable. These variances were influenced by several factors, including increases in minimum wages, holiday allowances, changes in working hours, and fluctuations in worker productivity. The study also found that inaccurate labor cost standards may affect the effectiveness of production cost control and managerial decision-making. Therefore, this study concludes that the company needs to improve its direct labor standard costing system in order to increase the accuracy of production cost calculations and support more effective managerial decisions. Keywords: cost of goods manufactured, cost variance, direct labor cost, standard costing.